Pengaruh Tingkat Bagi Hasil, Inflasi, dan Suku Bunga terhadap Deposito Mudharabah pada Perbankan Syariah di Indonesia - Muhammad Bahrul Ulum; Ayu Geby Gisela Syaputri (Prodi Bisnis Digital Fakultas Ekonomi Dan Bisnis, 2025)
This study aims to analyze the effect of profit-sharing rate, inflation, and interest rate on mudharabah deposits in Islamic banking in Indonesia. Mudharabah deposit is one of the main products of Islamic banks that applies a profit-sharing principle between the depositor (shahibul maal) and the bank (mudharib). The development of mudharabah deposits is often influenced by internal factors such as the profit-sharing rate, as well as external macroeconomic factors such as inflation and the Bank Indonesia interest rate. This research employs a quantitative approach using secondary data obtained from official publications of the Financial Services Authority (OJK), Bank Indonesia, and the Central Bureau of Statistics (BPS) over a certain period. The data were analyzed using multiple linear regression to examine the relationship and influence of independent variables (profit-sharing rate, inflation, and interest rate) on the dependent variable (mudharabah deposits). The results show that the profit-sharing rate has a positive and significant effect on mudharabah deposits, meaning that a higher profit-sharing rate increases public interest in placing their funds in Islamic banks. Meanwhile, inflation has a negative effect because higher inflation reduces purchasing power and the real value of returns. The interest rate has a negative and significant effect, indicating a substitution tendency from Islamic banks to conventional banks when interest rates rise. Overall, the findings confirm that macroeconomic stability and Islamic banking policy play an essential role in maintaining the growth of third-party funds through mudharabah deposits in Indonesia.